Constitutionalism as a Void Signifier at the Outskirts of World Society:: What can the category “State terrorismo” say about global constitutionalism? (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
The expansion the international security regime, especially regarding the fight against “terrorism”, has had significant, tough distinct effects over the constitutionalism in the centers and in the peripheries of world society. Because it represents tensions and intersections between foundational aspects of the modern legal and political systems, such as human rights, use of force violence and democracy, the concept of “state terrorism” offers an alternative entry point to observe terrorism and its consequences over the reproduction of the legal system. This paper attempts to offer a counterpoint to the dominant debate over transnational forms of constitutionalization that takes into account peripheral patterns of social reproduction and functioning of the law and the constitution in the peripheries of world society. To that end, I introduce the category of “peripheral constitutionalism”, which, far from introducing a “new constitutional concept”, outlines a research agenda that reacts to the current state of the debates over global constitutionalism by highlighting, rather than effacing, the center/periphery distinction at the very core of an observation of the legal system in world society. The paper establishes a dialogue with the debates over public security and human rights, global constitutionalism and international security regimes. Key words: state terrorism, constitucionalism, human rights, center/periphery.
Keywords: state terrorism; constitutionalism; human rights; center/periphery